Gambaran Radiologi pada Penyakit Rheumatoid Arthritis - Tasya Auliana Damanik; Laila Amalia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Rheumatoid arthritis (RA) is a daily disease seen in rheumatology clinics. It predominantly involves the appendicular skeleton. The axial skeleton is mostly spared except for the cervical spine where instability can occur and can be carefully assessed with cervical spine radiographs in flexion and extension. Radiographs may show erosion at the C1-C2 level with destruction of the transverse ligament that can result in atlantoaxial subluxation. Diagnosis is based on clinical, laboratory, and radiographic findings. Conventional radiography has been the mainstay for diagnosis of joint damage and subsequent follow-up. Radiography can provide only indirect information on synovial inflammation, however, and the technique is insensitive to early bone damage. Hand radiographs are frequently ordered as the first imaging modality in the assessment of patients presenting with peripheral arthritis. They can provide invaluable information about the bones, joints, mineralization, soft tissues and the distribution of abnormalities. Given the wide spectrum of rheumatic diseases, it might be challenging to make the diagnosis solely based on the clinical findings and imaging plays an important role in narrowing the differential diagnosis. Having the knowledge of the common radiographic manifestations of inflammatory arthritis is of paramount importance for clinicians and radiologists to diagnose the underlying disease in early stages of disease in order to start treatment. The purpose of the article is to review the key radiographic findings of common rheumatic diseases in the hands.